2019
DOI: 10.1063/1.5120352
|View full text |Cite
|
Sign up to set email alerts
|

A Boolean OR gate implemented with an optoelectronic switching memristor

Abstract: Nonvolatile stateful logic computing in memristors has tremendous potential to realize the aggregation combined with information storage and processing in the same physical location for breaking the von Neumann bottleneck of traditional computing architecture. Here, we fabricate a monoclinic BiVO4 film with a bandgap of Eg ≈ 2.4 eV and a nanoporous morphology as the memristor storage medium. The device, consisting of a TiN/BiVO4/fluorine-doped tin oxide structure, demonstrated excellent electric- and light-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…[ 16 − 19 ] Despite their excellent performances, two‐terminal optoelectronic memristors can respond to only one input signal from voltage bias, which restricts their applications for multilevel resistive switching memories and complex learning networks. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16 − 19 ] Despite their excellent performances, two‐terminal optoelectronic memristors can respond to only one input signal from voltage bias, which restricts their applications for multilevel resistive switching memories and complex learning networks. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…[16−19] Despite their excellent performances, two-terminal optoelectronic memristors can respond to only one input signal from voltage bias, which restricts their applications for multilevel resistive switching memories and complex learning networks. [20] Tremendous efforts have been made to achieve both memristive switching of the memristor and gate tunability of fieldeffect transistors, the so-called memtransistor, to provide an additional degree of freedom to control bistable resistance states. [21−24] Most popular technical approaches are associated with the manipulation of defects and grain boundaries in resistive switching materials.…”
mentioning
confidence: 99%
“…Performing this operation mandated a somewhat complex multistep process involving negative voltages. A Boolean OR gate implemented with an optoelectronic switching memristor was also shown by Zhao et al [ 26 ] This emerging research field presents an opportunity for the development of intelligent, bioinspired visual perception apparatuses. Such systems could replace both bionic prostheses [ 27 29 ] and robotic eyes, [ 30 ] combining image sensors with artificial intelligent image processing [ 31 , 32 ] into a single platform.…”
mentioning
confidence: 92%
“…15 Among recent reports, Yuqian Chen et al demonstrated a heterostructure of PtS 2 /h-BN/graphene as multibit optoelectronic memory, which performed up to 74 differentiable states (>6 bits) via controlled linear conductance using light pulses. 24 In concern with multifunction, specic operations are also performed within the memory devices such as arithmetical operation, 1,25 logic operation (function of digital logic gates: "AND", "OR", "NAND", "NOR"), 2,16,[26][27][28] and Pavlovian associative learning process. [29][30][31] Moreover, photomemrister 28,32,33 and photonic synapse 34 were also studied and reported.…”
Section: Introductionmentioning
confidence: 99%